Circular RNA detection methods: A minireview - Mi, Zhang; Zhongqiang, Chen; Caiyun, Jiang; Yanan, Liu; Jianhua, Wu; Liang, Liu (Talanta (Oxford), 2022)
Circular RNA (circRNA), a novel type of covalently closed RNA, is implicated in several developmental and metabolic disease processes. CircRNAs exhibit tissue-specific expression, and are stable, abundant, and highly conserved, making them ideal biomarkers for diagnosis and prognosis. Accurate profiling of circRNA, however, is a prerequisite for their clinical application. Traditional methods such as northern blotting, RT-qPCR, and microarray analysis provide useful but limited information. To address these issues, a number of novel assays have recently emerged, such as droplet digital PCR (ddPCR), isothermal exponential amplification, and rolling cycle amplification, which increase the sensitivity and specificity of circRNA detection. Herein, we summarize the advantages and limitations of the new detection methods and discuss the challenges as well as future directions. [Display omitted] •circRNA exhibit specific characteristics making them ideal biomarkers for diagnosis and prognosis.•Traditional methods such as northern blotting, RT-qPCR, and microarray analysis provide useful but limited information.•New techniques available for circRNA detection, such as RT-ddPCR, RCA, LAMP was described, including their advantages and limitations.•Technical challenges of as well as future directions of circRNA was discussed.